Radular marks produced by grazing gastropods of the rocky intertidal - Reyes, Yván (2001)
We had used artificial surfaces to examine the radular marks of four common grazing gastropods from Ancon Bay. In this work we show radular marks on dental wax surface of the trochid Tegula atra (Lesson, 1830), the fissurellid Fissurella peruviana Lamarck, 1822, the lottid Lottia ceciliana (Orbigny, 1841) and the littorinid Nodilittorina peruviana (Lamarck, 1822). In addition, the radular type is described to each species to relate it to the produced mark.